Distribution shifts, potential refugia, and the performance of protected areas under climate change in the Araucaria moist forests ecoregion. Issue 4 (13th December 2021) - Saraiva, Daniel Dutra; Esser, Luíz Fernando; Grasel, Daniel; Jarenkow, João André
Abstract: Aim: Araucaria moist forests are particularly vulnerable to climate change due to their strict climatic requirements and patchy distribution. Therefore, identifying areas where these forests are expected to lose or retain climatically suitable space (i.e., climate change refugia) is urgently required. Here, we modeled the current and future climatic suitability for Araucaria moist forests aiming: (a) to identify areas of suitable climate (i.e., in situ and ex situ refugia); (b) to identify areas of climate retraction; and (c) to assess the effectiveness of protected areas to capture climatically suitable space. Location: Araucaria moist forests ecoregion, southern Brazil and northeast Argentina. Methods: We mapped the potential distribution of Araucaria moist forests using an ensemble forecasting approach with 18 indicator tree species (all wet‐ and cold‐adapted taxa), six algorithms, eight global circulation models, three representative concentration pathways (RCPs 4.5, 6.0, and 8.5), and three periods (current, 2050, and 2070). Results: We predicted substantial losses of future climatic suitability across almost the entire range where these forests occur, ranging from 43% to 64% under optimistic (RCP4.5/2050) and high‐emissions (RCP8.5/2070) scenarios. We found that the protected‐areas network captured only 3% of the climatically suitable space under current conditions. We found that only 4% (top 1% of cells) and 12% (top 5% of cells) of the potential refugia would be protected in the future, with less than half of their areas corresponding to in situ refugia. Conclusions: Projected losses of potential distribution and the low efficacy of protected areas to buffer climate change impacts point to a high‐risk scenario for Araucaria moist forests in the near future. Cold‐adapted tree species likely will face increased extinction risk, especially as climate change will interact with other anthropogenic drivers. Abstract : We mapped the potential distribution of Araucaria moist forests to identify areas where these forests are expected to lose or retain climatic suitability by 2070. We found that climate change will greatly reduce suitability across almost the entire range where these forests occur and that the protected‐areas network is not effective (and will not be) in representing current and future suitability.